HUBUNGAN KEKUATAN OTOT LENGAN DAN KELENTUKAN TUBUH DENGAN HASIL PEMBELAJARAN HANDSTAND ROLL - Yusuf, Aswin; Surisman, Surisman; Sulistianta, Heru (JUPE, 2013)
This research is aimed to know the correlation between the strength of arm muscle and bodyÃ¢â¬â¢s flexibility with studentsÃ¢â¬â¢ achievement in gymnastic floor exercise at grade VIII students of YP Gajah Mada Bandarlampung. The population of this research was all students of YP Gajah Mada Bandarlampung consisting of 158 students which were taken about 40 men students as a sample. The sample was taken by proportional random sampling technique. The data of this research was taken by push-pull dynamometer, extension trunk, sit and reach flexibility and instrument descriptor. The data of this research was analyzed by multiple correlations. The results of this research are: first, there is a correlative coefficient around 0,900 which means that there is a positive correlation between the strength of arm muscle and students achievement in handstand roll.Penelitian ini bertujuan untuk mengetahui hubungan antara kekuatan otot lengan dan kelentukan tubuh dengan hasil pembelajaran handstand roll pada siswa kelas VIII YP Gajah Mada Bandarlampung. Populasi pada penelitian ini adalah seluruh siswa YP SMP Gajah Mada Bandarlampung berjumlah 158 siswa, dengan sampel yang digunakan 40 siswa putra menggunakan teknik proporsional random sampling. Teknik pengambilan data menggunakan push-pull dynamometer, extension trunk, sit and reach flexibility dan instrument descriptor. Teknik analisis data menggunakan korelasi ganda (multiple correlation). Hasil penelitian menunjukan : Pertama, diperoleh koefisien korelasi sebesar 0,900 artinya ada hubungan yang positif/sangat kuat kekuatan otot lengan dengan hasil pembelajaran handstand roll.Kata kunci: kekuatan, kelentukan, handstand Roll